Spatio-Temporal Analysis Of Road Insecurity In Algeria: Case Of The Wilaya Of Oum El Bouaghi During The Period 2017-2019 - Aissaoui , Nasreddine (Finance and Business Economies Review, 2022)
We aim to analyze the characteristics and specifics of the road accident in the wilayas of Oum El Bouaghi, by emphasizing the space and time of the occurrence of traffic accidents on the roads of this wilaya. We arrived at several results, among them: the most populated daïras are the places which register more victims (Ain Beida, Oum El Bouaghi, Ain Mlila and Ain Fakroun), this confirms that the human factor is primarily responsible for road insecurity in Algeria; the national roads are the most deadly among the roads of the wilaya OEB; the summer vacation period, the weekend departure and return days and the return-to-work hours at the end of the day are the most risky periods and times on the roads of this wilaya.